CuO metallic aerogels with a tailored nodular morphology - Dos-Santos-Gómez, Lucía; Rey-Raap, Natalia; Garcia-Granda, Santiago; Arenillas, Ana (RSC (Royal Society of Chemistry), 2023)
This work reports, for the first time, an efficient and fast microwave-based method for the preparation of CuO aerogels. For that, CuCl2, glyoxylic acid and sodium carbonate are employed as reagents. Different experimental conditions such as synthesis temperature, synthesis time and concentration of the precursor solution are investigated to design CuO aerogels with customizable nodular morphologies. The resulting aerogels exhibit well-defined three-dimensional structures and nodular sizes, and therefore, textural properties vary according to the experimental parameters applied in their synthesis.
Keywords: Química Inorgánica; Química Inorgánica